Contribution of physical fitness and motivation to student learning outcomes - Mulyadi, Sandi; Kurniadi, Dendi; Amalia, Eneng Fitri (Jurnal Maenpo : Jurnal Pendidikan Jasmani Kesehatan dan Rekreasi, 2024)
The aim of the study was to examine the contribution of physical fitness and student learning motivation to student learning outcomes in sports psychology courses for PJKR FKIP students at Suryakancana University, Cianjur. The research method used is the ex post facto method with correlational techniques. The result is that; 1) There is a significant contribution of physical fitness to learning outcomes in sports psychology courses for students; 2) There is a significant contribution of learning motivation to learning outcomes in sports psychology courses for students; 3) There is a significant contribution of physical fitness and student learning motivation to learning outcomes in sports psychology courses for PJKR FKIP Suryakancana Cianjur students. Thus, it can be concluded that the level of physical fitness and student learning motivation can contribute significantly to improving learning outcomes in sports psychology courses for PJKR FKIP University Suryakancana Cianjur students. In this regard, to improve student learning outcomes, it is necessary to develop planned and regular physical conditions to build fitness and increase learning motivation so that in the end it will support the achievement of better student learning outcomes